2022
DOI: 10.1111/jce.15681
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation of atrial fibrillation—50 W or 90 W?

Abstract: Background: This study sought to evaluate the short and midterm efficacy and safety of the novel very high power very short duration (vHPvSD) 90 W approach compared to HPSD 50 W for atrial fibrillation (AF) ablation as well as reconnection patterns of 90 W ablations. Methods and Results: Consecutive patients undergoing first AF ablation with vHPvSD (90 W; predefined ablation time of 3 s for posterior wall ablation and 4 s for anterior wall ablation) were compared to patients using HPSD (50 W; ablation index-gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…It is important to note that whilst these parameters are excellent acute markers for clinical efficacy, they are not a substitute for clinical outcome data on follow up. In this edition of the Journal of Cardiovascular Electrophysiology , Mueller and colleagues present the results of a single center, retrospective, propensity matched study comparing 12‐month outcomes of ablation with 90 W (vHPvSD) versus Ablation Index (AI) guided 50 W (sRF) in 84 patients 4 . They found that 90 W vHPvSD ablation was associated with shorter ablation times (10.5 vs. 17.4 min; p = .001), but with lower FPI rates (40% vs. 62%; p = .049), higher AF recurrence during the blanking period (38% vs. 12%; p = .007), and a trend towards a lower freedom from AF at 12 months (62% vs. 75%; p = .071).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that whilst these parameters are excellent acute markers for clinical efficacy, they are not a substitute for clinical outcome data on follow up. In this edition of the Journal of Cardiovascular Electrophysiology , Mueller and colleagues present the results of a single center, retrospective, propensity matched study comparing 12‐month outcomes of ablation with 90 W (vHPvSD) versus Ablation Index (AI) guided 50 W (sRF) in 84 patients 4 . They found that 90 W vHPvSD ablation was associated with shorter ablation times (10.5 vs. 17.4 min; p = .001), but with lower FPI rates (40% vs. 62%; p = .049), higher AF recurrence during the blanking period (38% vs. 12%; p = .007), and a trend towards a lower freedom from AF at 12 months (62% vs. 75%; p = .071).…”
Section: Introductionmentioning
confidence: 99%
“…versus Ablation Index (AI) guided 50 W (sRF) in 84 patients. 4 They found that 90 W vHPvSD ablation was associated with shorter ablation times (10.5 vs. 17.4 min; p = .001), but with lower FPI rates (40% vs. 62%; p = .049), higher AF recurrence during the blanking period (38% vs. 12%; p = .007), and a trend towards a lower freedom from AF at 12 months (62% vs. 75%; p = .071).…”
mentioning
confidence: 99%
“…In cardiac EP, there have been several studies using least squares regression to predict different outcomes, ranging from predicting the likelihood of AF recurrence to what wattage catheter ablations perform better. [9][10][11][12][13][14][15] Least squares regressions have been preferred in these studies because they are easy to implement, can learn the key features (from EHR data/clinical covariates or ECG biomarkers, or in performing survival analysis), and are interpretable. Least squares regressions are often included with other ML algorithms to help find the best performing model.…”
Section: Least Squares Regressionmentioning
confidence: 99%
“…[5][6][7][8][9] Recently, a very HPSD (vHPSD; 90 W, 4 s) technique has been introduced, but initial efficacy results were mostly discouraging regarding first-pass isolation rates, acute reconnection rates, and arrhythmia-free survival. [10][11][12][13][14] We hypothesized that vHPSD PVI could result in similar acute and long-term efficacy as ablation indexguided PVI with 50 W. 11 Therefore, we designed the HPSD Remap study (Efficacy Comparison of High and Very High Power Short Duration Pulmonary Vein Isolation, URL: https://www.clinicaltrials.gov; unique identifier NCT05459831), in which durability of lesions was assessed by a repeat electrophysiology study after an index PVI performed with either a 90-or 50-W power setting.…”
mentioning
confidence: 99%
“…5–9 Recently, a very HPSD (vHPSD; 90 W, 4 s) technique has been introduced, but initial efficacy results were mostly discouraging regarding first-pass isolation rates, acute reconnection rates, and arrhythmia-free survival. 10–14…”
mentioning
confidence: 99%